PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS CANVA UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS V SDN 56/I DESA ARO PADA PEMBELAJARAN IPAS - Afdiya, Putri; Syahrial; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the engagement and learning outcomes of fifth-grade students at SDN 56/I in Aro Village in their IPAS lessons through the use of Canva-based learning media. The research design employed in this study is classroom action research (PTK). Data for this study were collected through observations and interviews. The data were then analyzed both qualitatively and quantitatively. This study was conducted in two cycles, consisting of four stages: planning, implementation, observation, and reflection. Based on the results of the study, the use of a Canva-based learning model was found to improve student engagement and learning outcomes in IPAS lessons. The results from the first session of Cycle I showed a percentage of 47.52, categorized as “Low,” while the second session of Cycle I yielded a percentage of 64.26%, categorized as “Moderate,” representing an increase of 16.47%. In the first session of Cycle II, a percentage of 76.05% was achieved, falling into the “High” category—representing an increase of 11.79%—and in the second session of Cycle II, a percentage of 82.26% was achieved, also falling into the “High” category, with an increase of 6.21%. The results from the second session of Cycle II had already reached the success indicator threshold of 70%. Furthermore, student learning outcomes also improved: in the first session of Cycle I, only 5 out of 19 students met the minimum competency standard (KKM); whereas in the second session of Cycle II, all 19 students met the KKM. Based on these research findings, it can be concluded that the use of Canva-based learning media can enhance student engagement and learning outcomes for fifth-grade students at SDN 56/I in Aro Village in their IPAS lessons